Dasatinib discontinuation in patients with chronic-phase chronic myeloid leukemia and stable deep molecular response: the DASFREE study. Issue 3 (23rd February 2020) - Shah, Neil P.; García-Gutiérrez, Valentín; Jiménez-Velasco, Antonio; Larson, Sarah; Saussele, Susanne; Rea, Delphine; Mahon, François-Xavier; Levy, Moshe Yair; Gómez-Casares, María Teresa; Pane, Fabrizio; Nicolini, Franck-Emmanuel; Mauro, Michael J.; et al.
Abstract: Treatment-free remission (TFR) in patients with chronic myeloid leukemia in chronic phase (CML-CP) is considered a feasible option, especially with the ability of second-generation tyrosine kinase inhibitors to induce higher rates of sustained deep molecular response (DMR). DASFREE is an open-label, single-arm, multicenter phase II trial assessing TFR after dasatinib discontinuation in patients with CML-CP ( N = 84). At 2 years, TFR was 46% in all patients. Multivariate analyses revealed statistically significant associations between 2-year TFR and duration of prior dasatinib (≥median; p = .0051), line of therapy (first line; p = .0138), and age (>65 years; p = .0012). No disease transformation occurred, and the most common adverse events experienced off treatment were musculoskeletal (observed in 30 patients); however, dasatinib withdrawal events were reported in nine patients (11%) by the investigator. Overall, these findings support the feasibility of discontinuing dasatinib for patients with CML-CP in sustained DMR in the first line and beyond.